1995
DOI: 10.21273/hortsci.30.5.1074
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Regeneration in Vitro from Diverse Genotypes of Sweetpotato and Multiple Shoot Production per Explant

Abstract: Studies were conducted to improve adventitious shoot regeneration in sweetpotato [Ipomoea batatas (L.) Lam.], specifically to extend the protocol to many genotypes and to elicit production of multiple shoots per explant. The use of a two-stage procedure where excised petioles were incubated on Murashige and Skoog (MS) (1962) medium with 2,4-D (0.2 mg·liter–1) for 3 days and transferred to a second medium containing MS salts with thidiazuron and 2iP (0.05 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
3
1
1
Order By: Relevance
“…resulted in the highest number of cultivars producing multiple shoots. Contrary to our results, other studies reported multiple shoots on media supplemented with TDZ (Gosukonda et al, 1995b;Sefasi et al, 2013). Differences in results could be attributed to the type of cytokinin used and genotypic variations.…”
Section: Genotype and Cytokinin Dependentcontrasting
confidence: 99%
See 1 more Smart Citation
“…resulted in the highest number of cultivars producing multiple shoots. Contrary to our results, other studies reported multiple shoots on media supplemented with TDZ (Gosukonda et al, 1995b;Sefasi et al, 2013). Differences in results could be attributed to the type of cytokinin used and genotypic variations.…”
Section: Genotype and Cytokinin Dependentcontrasting
confidence: 99%
“…Differences in results could be attributed to the type of cytokinin used and genotypic variations. This notwithstanding, a number of multiple shoots were produced on media containing TDZ in our study, a results reported by Gosukonda et al (1995b) and Sefasi et al (2013).…”
Section: Genotype and Cytokinin Dependentsupporting
confidence: 86%
“…Shoot tips are generally preferred for embryogenic procedures (Cavalcante et al 1994;Padmanabhan et al 1998) but leaves, petioles, roots and stems have also been used (Cheng and Yeh 2003;Gong et al 2005). Alternatively, rapid shoot-organogenesis has been obtained from leaf explants Gosukonda et al 1995). Besides tissue regeneration procedures, methods to produce transgenic sweetpotato plants have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Bir çözüm yöntemi olarak in vitro şartlarda çoğaltım, çok sayıda sağlıklı ve uniform bitkiler elde etmeye olanak sağlamaktadır. Tatlı patates somatik embriyogenesis ve harici tomurcuklar yardımıyla apikal ve aksiller tomurcukların gelişimi uyarılarak çoğaltılabilmektedir (Gosukonda et al, 1995, González et al, 1999, Mukherjee, 2002. Ticari alanlar için tohumluk materyali üretmede tomurcuklu eksplantların kullanıldığı teknikler en etkili yöntemlerdendir.…”
Section: Introductionunclassified